Destabilisation and cultural literacy. Issue 4 (4th July 2019) - García Ochoa, Gabriel; McDonald, Sarah
ABSTRACT: There is a growing body of work on the field of what is now known as 'cultural literacy', but little has been written about its application, and even less on how to teach it in the context of higher education. This article discusses 'destabilisation' as an approach to teaching cultural literacy in higher education in the context of the global challenges that universities face today. It defines the characteristics of destabilisation and highlights its advantages in relation to other teaching approaches that have a similar focus on developing cultural competence in students. The article also situates 'destabilisation' as a pedagogical term within a spectrum of experiential learning methods and techniques that are focused on developing cultural competence.